Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Anggota Dimediasi Kepuasan pada KSP Kopdit Obor Mas Cabang Hokeng - Delius Moan Pehan; Khuzaini Khuzaini; Bambang Hadi Santoso (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the Influence of service quality and trust on members’ loyalty in the Savings and Loan Cooperative Kopdit Obor Mas Hokeng Branch, with member satisfaction as a mediating variable. The method used in this study is a quantitative approach with regression analysis involving 100 active cooperative members who meet certain criteria. The study’s results indicate that service quality has a positive and significant effect on both member satisfaction and loyalty. In addition, member trust has a positive and significant effect on loyalty, but does not significantly affect member satisfaction. Member satisfaction has been shown to mediate the effect of service quality on member loyalty. However, member satisfaction does not mediate the effect of trust on loyalty, indicating that members’ trust more directly influences loyalty in the cooperative. This study contributes to understanding the importance of service quality and trust in building cooperative member loyalty. It provides recommendations for KSP Kopdit Obor Mas Hokeng Branch to continually improve service quality to strengthen long-term relationships with its members.